A blind image watermarking algorithm based on amalgamation domain method. (17th June 2019) - Su, Qingtang
Combining with the spatial domain and the frequency domain, a novel blind digital image watermarking algorithm is proposed to resolve the protecting copyright problem in this paper. When embedding watermark, the generation principle and distribution features of direct current (DC) coefficient are utilised to directly modify the pixel values in the spatial domain, then four different sub-watermarks are embedded into different areas of the host image for four times, respectively. When extracting watermark, the sub-watermark is extracted with blind manner according to DC coefficients of watermarked image and the key-based quantisation step, and then the statistical rule and "first to select, second to combine" are proposed to form the final watermark. Hence, the proposed algorithm not only has the simple and quick performance of the spatial domain but also has the high robustness feature of DCT domain. Many experimental results have proved that the proposed watermarking algorithm has good invisibility of watermark and strong robustness for many added attacks, e.g., JPEG compression, cropping, adding noise, etc. Comparison results also have shown the benefits of the proposed algorithm.